Cluster anxiety-related adverse events following immunization (AEFI): An assessment of reports detected in social media and those identified using an online search engine. Issue 40 (25th September 2018) - Suragh, Tiffany A.; Lamprianou, Smaragda; MacDonald, Noni E.; Loharikar, Anagha R.; Balakrishnan, Madhava R.; Benes, Oleg; Hyde, Terri B.; McNeil, Michael M.
Abstract: Background: Adverse events following immunization (AEFI) arising from anxiety have rarely been reported as a cluster(s) in the setting of a mass vaccination program. Reports of clusters of anxiety-related AEFIs are understudied. Social media and the web may be a resource for public health investigators. Methods: We searched Google and Facebook separately from Atlanta and Geneva to identify reports of cluster anxiety-related AEFIs. We reviewed a sample of reports summarizing year, country/setting, vaccine involved, patient symptoms, clinical management, and impact to vaccination programs. Results: We found 39 reports referring to 18 unique cluster events. Some reports were only found based on the geographic location from where the search was performed. The most common vaccine implicated in reports was human papillomavirus (HPV) vaccine (48.7%). The majority of reports (97.4%) involved children and vaccination programs in school settings or as part of national vaccination campaigns. Five vaccination programs were reportedly halted because of these cluster events. In this study, we identified 18 cluster events that were not published in traditional scientific peer-reviewed literature. Conclusions: Social media and online search engines are useful resources for identifying reports of cluster anxiety-related AEFIs and the geographic location of the researcher is an important factor to consider when conducting these studies. Solely relying upon traditional peer-reviewed journals may seriously underestimate the occurrence of such cluster events.